A nutritional and financial evaluation of breeding African Grey parrots (Psittacus erithacus) - Dennison, D. T. (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPhil (Animal Sciences))--University of Stellenbosch, 2004.